PENGARUH SERTIFIKASI JABATAN FUNGSIONAL DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT PADA INSPEKTORAT JENDERAL DEPARTEMEN PENDIDIKAN NASIONAL - Sudjono Sudjono (Universitas Bunda Mulia, 2017)
This research purpose is to find out and to analysis (1) the impact of auditor certification on audit quality, (2) the impact of auditor independency on audit quality, and (3) the impact of auditor certification and auditor independency simultantly on audit quality.The methodology applied is statistic, empirical, and cross-sectional. The analysis technique applied is non parametric test with assistance of SPSS 10.5. Research population is internal auditors government in Inspectourat General National Education Department, and the research sample are certified auditor functional holder. Data collection method is direct survey to respondents by questionare, sent 72 questionare and received 60 questionare processed. Statistical test in this research are data quality test, classical assumption test and hypothesis test. Result of analysis are: (1) Auditor certification proven influence significantly on audit quality, (2) auditor independence influence not significantly on audit quality, and (3) auditor certification and auditor indepndency simultanly influence significantly on audit quality.This research resulted same conclution with other research held by Esron (2008), Christiawan (2005), and Solichin (2008) about impact competence, training, and auditor independency on audit quality, who taked respondent are certified public accountant and auditors in BPK.Keywords: Certification, auditor functional holder, independency, quality of audit, internal auditor of government, standard of audit.